How Globalization Influences the Developing Countries’ Human Resources Strategic Policy - Asadi, Rahil; Marin, Gabriel Octavian (Journal of Economic Development, Environment and People, 2019)
Development of human resources is one of the key issues of today's economics and management scholars. Starting from the basic concepts of human resources – definition, trends of development, related indicators the present research evolves under three components: education, life expectancy and gross domestic product per capita. Figures that sustains our demarche flow according to the ranking data in terms of globalization index and The United Nations Human Development Index (HDI), calculated with the STATGRAF statistical software. We used the Spearman correlation coefficient and correlated the intensity between the two variables (R=76%), to show the close relationship between the Globalization Index and Human Resource Development. Taking such conclusions into consideration could make more successful the advances in the field of human resources.